An Evaluation of Grassland Management Practices for Wildlife in Central Wisconsin - Halvorsen, Harvey H. (University of Wisconsin-Stevens Point, College of Natural Resources, 1981)
This study was conducted during 1977 and 1978 to evaluate grassland management techniques on selected parts of a 4765-ha prairie chicken (Tympanuchus cupido pinnatus) management area within the Buena Vista Marsh in central Wisconsin. Plants were inventoried in randomly located permanent quadrats in treatment and control plots the growing season before and after treatments. Small mammals and birds were censused on treatment and control plots before (1977) and after (1978) burning; insect populations were monitored on burned and control plots in 1978. Controlled burning had no effect on plant species composition. Spring burning (late March - early April) maintained the dominant cool season grasses, Kentucky bluegrass (Poa pratensis) and quackgrass (Agropyron repens), without reducing their density, frequency of occurrence, percent cover, or standing crop. Burning significantly increased the moisture content of grasses from May through July, but did not affect foliar nutrient composition throughout the growing season. In this study, burning did not control or convert dense stands of perennial forbs (Solidago spp.) or shrubs (Spiraea alba) into earlier grass-forb successional stages. These plants reproduce by underground rhizomes and are relatively unaffected by the present burning program. Post burn density of savannah sparrows ( Passerculus sandwichensis) and clay-colored sparrows (Spizella pallida) declined 80 and 94% respectively. Fire-altered habitat did not affect the relative abundance of meadow voles (Microtus pennsylvanicus) or short-tailed shrews (Blarina brevicauda), increased the relative abundance of deer mice (Peromyscus maniculatus) and meadow jumping mice (Zapus hudsonius), but reduced the combined relative abundance of masked shrews (Sorex cinereus) and pigmy shrews (Microsorex hoyi). Arthropod biomass and density sweep-netted on burned and unburned grasslands were not significantly different. Herbicide treatment significantly reduced the density and percent cover of goldenrod (Solidago spp.). Plant species composition was unaltered by chemical treatment. Percent cover of quackgrass increased significantly on sprayed plots the growing season following application. Mowing had no statistically significant effects on stem density or percent cover of quackgrass, Kentucky bluegrass, forbs or shrubs. Plant species composition and frequency of occurrence were unaltered by mowing. Stem density and height of timothy increased significantly after mowing. Plowing and disking significantly reduced the stem density and percent cover of Kentucky bluegrass and meadowsweet (Spiraea alba), but had no effect on percent cover of quackgrass or reed canary grass (Phalaris arundinacea) the first growing season after disturbance. Revegetation of the plowed plot occurred chiefly by regeneration of perennial plant root fragments present in the soil. Because of this pattern of regrowth, interspersion of dominant vegetation was similar before and after disturbance. Plowing effectively improved the grass-forb composition within a previously dense meadowsweet cover type. Soil disturbance also increased plant species composition and enhanced the flowering vitality of quackgrass.